The Pendulum of Strife: Cyclical Activation, , and the Political Economy of the Tanzania-Malawi Territorial Dispute (1964–2025) - Augustus Caesar Rwelengera; Jacob Joachim Lisakafu; Miraji Kitigwa (Pinisi Journal of Social Science, 2026)
This paper challenges the conventional framing of the Tanzania-Malawi territorial dispute as a static legal conflict rooted in the ambiguities of the 1890 Anglo-German Heligoland Treaty. It proposes a novel cyclical model of activation and dormancy to explain the dispute's intermittent intensity over six decades. Moving beyond a purely legal analysis, the study employs a political economy lens to argue that the conflict's volatility is primarily driven by the domestic political calculations and economic imperatives of governing elites in both nations. Utilising primary sources from national archives, parliamentary records, and stakeholder interviews, the paper identifies three distinct phases: intense activation in the 1960s and 1970s fuelled by clashing presidential ideologies; a prolonged dormancy from 1975 to 2010 marked by diplomatic normalisation and robust local cross-border trade; and a sharp reactivation in 2011 triggered by the discovery of hydrocarbon resources. A key finding is that during dormancy, the border successfully decouples from state politics, becoming a site of deep socio-economic interdependence that state-level animosities fail to sever. The central thesis contends that reactivation is a strategic elite tool used to divert public attention from domestic crises or to capture sudden economic opportunities, not to resolve legal claims. The study concludes that international mediation fails because it addresses legal symptoms rather than these political-economic drivers. Successor administrations also lack the will to resolve an inherited issue that can be easily ignored or weaponised, perpetuating a cycle of deliberate ambiguity. This model offers a new framework for analysing other dormant border disputes, highlighting the primacy of domestic political economy over international law.